1997
DOI: 10.1038/sj.onc.1200870
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations can inactivate in vitro and in vivo activities of p16INK4a/CDKN2A in human glioma

Abstract: Deletions of chromosomal region 9p21 are among the most common genetic alterations observed during the clonal evolution of high grade malignant gliomas. Structural and functional evidence has suggested that homozygous deletion involving CDKN2A (the genetic locus encoding the cyclin-dependent kinase inhibitor p16 INK4a ) is a mechanism of inactivation of this gene and that it can be a growth suppressor in human gliomas. However, the presence of other potential suppressor genes in the 9p21 region and the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 11 publications
(31 reference statements)
2
41
0
Order By: Relevance
“…Similarly, our functional data imply that H98Y is not a mutant and the same conclusion was drawn recently by Arap et al in a survey of glioma-associated sequence variants (Arap et al, 1997). This contrasts with H98P which we and others have shown to be functionally defective (Koh et al, 1995;Parry and Peters, 1996;Zhang and Peng, 1996).…”
Section: Relative Merits Of Functional Assays For P16 Ink4asupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, our functional data imply that H98Y is not a mutant and the same conclusion was drawn recently by Arap et al in a survey of glioma-associated sequence variants (Arap et al, 1997). This contrasts with H98P which we and others have shown to be functionally defective (Koh et al, 1995;Parry and Peters, 1996;Zhang and Peng, 1996).…”
Section: Relative Merits Of Functional Assays For P16 Ink4asupporting
confidence: 90%
“…To try to address this possibility, we explored alternative assays based on ectopic expression of p16 INK4a sequences in eukaryotic cells. Several procedures have been described that use two types of readout: the ability of p16 INK4a to cause a G1 cell cycle arrest in transfected cells (Koh et al, 1995;Lukas et al, 1995;Shapiro et al, 1995;Parry and Peters, 1996;Arap et al, 1997) and the interaction of p16 INK4a with either endogenous or exogenous CDKs (Reymond and Brent, 1995;Shapiro et al, 1995;Yang et al, 1995;Castellano et al, 1997b). One example of the latter approach would be the yeast two hybrid system, which has been used to some e ect both in the initial identi®cation of p16 INK4a (Serrano et al, 1993) and in the functional evaluation of mutants (Reymond and Brent, 1995;Yang et al, 1995).…”
Section: Ectopic Expression Of P16 Ink4a Variants In Tig-er Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some germline mutations a ecting p16 INK4a in melanoma-prone persons (Hussussian et al, 1994;Gruis et al, 1995;Washimi et al, 1995;Fitzgerald et al, 1996), exclusively target exon 2 of the INK4a gene, apparently without a ecting p19 ARF function . These mutations prevent p16 INK4a from binding CDK4 (Ranade et al, 1995;Koh et al, 1995;Yang et al, 1995;Arap et al, 1997). Conversely, mutations in CDK4 that prevent INK4 binding have also been found in human melanomas (WoÈ lfel et al, 1995;Ruas and Peters, 1998).…”
Section: Ink4 Mutations In Human Tumorsmentioning
confidence: 99%
“…CDKN2B is frequently homozygously or heterozygously deleted together with CDKN2A in a variety of tumour cell lines and primary tumours (Hirama and Koe er, 1995). Overexpression of p15 is able to block cell cycle progression in G1 (Arap et al, 1997;McConnell et al, 1998;Stone et al, 1995). We have recently found that overexpression of p15 from an adenovirus vector, blocks cell proliferation, induces replicative senescence, and downregulates telomerase activity similarly to p16 (Fuxe et al, 2000 unpublished results).…”
mentioning
confidence: 96%